Language attitudes towards Hong Kong English : A comparison of direct and indirect measures - Li, Shengnan; Ting, Su Hie (2022)
In sociolinguistic studies, language attitudes have been described as the perception and value judgments that people ascribe to language varieties (Hidalgo 1986) and the speakers of these varieties (Anderson & Toribio, 2007; Fasold, 1987; Galindo, 1995). Previous studies on language attitudes have shown that in many Asian countries, English learners perceive American or British variety more positively than local varieties. Hong Kong English as an outer circle variety (Kachru, 1992), has been compared with inner circle and expanding circle varieties (e.g., Kim, 2007; Zhang, 2009). However, little is known about Chinese mainland people’s attitude towards Hong Kong English. Considering the cultural and economic differences between China and Hong Kong which has given rise to certain tensions, the present study examined attitudes of Chinese undergraduates towards Hong Kong English accent when spoken by male and female speakers using direct and indirect measures.